High weekly integral dose and larger fraction size increase risk of fatigue and worsening of functional outcomes following radiotherapy for localized prostate cancer - Joseph, Nuradh; Cicchetti, Alessandro; McWilliam, Alan; Webb, Adam; Seibold, Petra; Fiorino, Claudio; Cozzarini, Cesare; Veldeman, Liv; Bultijnck, Renée; Fonteyne, Valérie; Talbot, Christopher J.; Symonds, Paul R.; et al. (Frontiers in Oncology, 2022)
Introduction We hypothesized that increasing pelvic integral dose and higher dose per fraction correlate with worsening fatigue and functional outcomes in localized prostate cancer (PCa) patients treated with external beam radiotherapy (EBRT). Methods The study design was a retrospective analysis of two prospective observational cohorts, REQUITE (development, n=543) and DUE-01 (validation, n=228). Data were available for comorbidities, medication, androgen deprivation therapy, previous surgeries, smoking, age and body mass index. Integral dose (ID) was calculated as the product of mean body dose and body volume. Weekly ID accounted for differences in fractionation. Worsening (end of radiotherapy versus baseline) of EORTC QLQ-C30 scores in physical/role/social functioning and fatigue symptom scales were evaluated and two outcome measures defined as worsening in ≥2 (WS2) or ≥3 (WS3) scales, respectively. Weekly ID and clinical risk factors were tested in a multivariable logistic regression analysis. Results In REQUITE WS2 was seen in 28% and WS3 in 16% of patients. The median weekly ID was 13.1 L∙Gy/week (interquartile range 10.2-19.3). Weekly ID, diabetes, use of intensity modulated radiotherapy and dose per fraction were significantly associated with WS2 (AUC=0.59; 95% CI 0.55-0.63) and WS3 (AUC=0.60; 95% CI 0.55-0.64). The prevalence of WS2 (15.3%) and WS3 (6.1%) were lower in DUE-01, but the median weekly ID was higher (15.8 L∙Gy/week; interquartile range 13.2-19.3). The model for WS2 validated with reduced discrimination (AUC=0.52 95% CI 0.47-0.61), AUC for WS3 was 0.58, Conclusion Increasing weekly ID and dose per fraction lead to worsening of fatigue and functional outcomes in patients with localized PCa treated with EBRT.